La exclusión cognitiva y moral de la naturaleza en el pensamiento social clásico - Lezama, José Luis (El Colegio de México A.C., 2022)
In this article, we propose that the Classics carried out a process of exclusion of nature as a constitutive factor of the social and as an object of moral consideration. We are speaking here of an exclusion that obeys epistemological and ontological motivations, in which a double foundational need is expressed: on the one hand, of sociology as a scientific discipline and, on the other, of modern industrial society as a historical form of economic and social organization. We conclude that ontological exclusion leads to a moral exclusion that only the environmental crisis and its political and cognitive effect correct.